2020
DOI: 10.3390/jmse8050369
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Algorithm for Onboard Progressive Flooding Simulation

Abstract: The need for decision support after a flooding casualty requires the development of fast and accurate progressive flooding simulation procedures. Here, a new quasi-static technique is presented, proposing a differential algebraic formulation capable to consider independently the flooding process in the internal rooms. The proposed method is efficient while simulating long flooding chains along rooms connected by similar size openings, a condition that likely occurs on large passenger ships. Moreover, the compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In a previous study [17], it was observed that the longitudinal position of the damage center has only a limited impact on progressive flooding, whereas its vertical position has a relevant effect. Hence, all the single-room damages were applied at half of the room longitudinal extension assuming an L d equal to the room longitudinal extension.…”
Section: Parametric Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…In a previous study [17], it was observed that the longitudinal position of the damage center has only a limited impact on progressive flooding, whereas its vertical position has a relevant effect. Hence, all the single-room damages were applied at half of the room longitudinal extension assuming an L d equal to the room longitudinal extension.…”
Section: Parametric Methodsmentioning
confidence: 90%
“…In the present section, several options are proposed to generate the training database according to a different characterization of the damages. All the progressive flooding simulations were carried out using a quasi-static technique based on the solution of a linearized differential-algebraic equation system [18,19]. The method represents a good compromise between accuracy and computational effort [20]; hence, it was considered adequate for the generation of large databases of progressive flooding simulations.…”
Section: Database-generation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, F is the number of columns of the spectrum matrix, which can be calculated using Equation (13). s H n.m.i refers to the entry of the i-th row in the m-th p-vector among the spectrum matrix of the n-th case of heave motion in the ship motion database.…”
Section: Rmse To Predict Damage Centermentioning
confidence: 99%
“…The development of time-domain progressive flooding simulation tools is underway, which is operated on board as a way to help decision makers make decisions after detecting flooding locations [6][7][8][9][10][11][12][13]. These simulation tools implement virtually progressive flooding scenarios in a complex onboard structure.…”
Section: Introductionmentioning
confidence: 99%